Mnemonic effects of Fixed Oil of Black Cumin (Nigella sativa) seeds on aged rats with memory impairment - Azzubaidi, Marwan Saad; A.Talib, Norlelawati; Saxena, Anil Kumar; Ahmed, Qamar Uddin (2011)
Introduction: Memory and learning impairments in elderly remain an unsolved problem especially to those with vascular risk factors that accelerate the oxidative stress associated with aging. Fixed oil of Nigella sativa NSO (black cumin) has revealed considerable antioxidant, anti-inflammatory and immunomodulatory properties that may prevent or arrest the deterioration of cognitive brain function. Two vessel occlusion (2VO) surgery is broadly used to create cerebral hypoperfusion for studying cognitive impairment in rats. Objective: In this study Morris water maze (MWM) was used to compare the memory and learning performance of rats with memory and learning deficits induced by 2VO surgery with those orally treated with the NSO as well as with healthy sham control group. Methodology: Sixty rats were recruited in this study. Thirty animals were assigned for long term memory (LTM) test and a similar number was assigned for short term memory (STM) and learning (working memory) tests. Each of these main groups was subdivided into three subgroups each with ten rats. The first was the untreated 2VO, the second was the untreated sham control and the third was the orally NSO treated 2VO group. Results: For LTM and STM MWM test, both Sham control and NSO treated groups showed significantly better performance as compared to untreated 2VO group, confirmed with probe memory test one day later. For Working Memory MWM test, NSO treated groups had significantly lower escape latency time and total distance travelled (p<0.01) as compared to untreated 2VO on three successive test days. Conclusion: The seeds of Nigella sativa may have potential memory and learning enhancing activity and a prospective neuroprotective effect that requires further investigations on brain tissue probably through collaborative work with researchers from USM, University of Sydney or University of Queenland that could enable us to unveil the neuroprotective potential of Nigella sativa fixed oil. Keywords: Morris water maze, rats,2VO, memory, learning, Nigella sativa fixed oil.